Identification of Chemosensory Genes, Including Candidate Pheromone Receptors, in Phauda flammans (Walker) (Lepidoptera: Phaudidae) Through Transcriptomic Analyses - Hu, Jin; Wang, Xiao-Yun; Tan, Liu-Su; Lu, Wen; Zheng, Xia-Lin (Frontiers in Physiology, 2022)
Olfactory and gustatory systems play an irreplaceable role in all cycles of growth of insects, such as host location, mating, and oviposition. Many chemosensory genes in many nocturnal moths have been identified via omics technology, but knowledge of these genes in diurnal moths is lacking. In our recent studies, we reported two sex pheromone compounds and three host plant volatiles that play a vital role in attracting the diurnal moth, Phauda flammans. The antennal full-length transcriptome sequence of P. flammans was obtained using the Pacbio sequencing to further explore the process of sex pheromone and host plant volatile recognition in P. flammans. Transcriptome analysis identified 166 candidate olfactory and gustatory genes, including 58 odorant-binding proteins (OBPs), 19 chemosensory proteins (CSPs), 59 olfactory receptors (ORs), 16 ionotropic receptors (IRs), 14 gustatory receptors (GRs), and 2 sensory neuron membrane proteins (SNMPs). Subsequently, a phylogenetic tree was established using P. flammans and other lepidopteran species to investigate orthologs. Among the 17 candidate pheromone receptor (PR) genes, the expression levels of PflaOR21, PflaOR25, PflaOR35, PflaOR40, PflaOR41, PflaOR42, PflaOR44, PflaOR49, PflaOR51, PflaOR61, and PflaOR63 in the antennae were significantly higher than those in other non-antennae tissues. Among these PR genes, PflaOR21, PflaOR27, PflaOR29, PflaOR35, PflaOR37, PflaOR40, PflaOR42, PflaOR44, PflaOR60, and PflaOR62 showed male-biased expression, whereas PflaOR49, PflaOR61, and PflaOR63 revealed female-biased expression. The functions of related OR genes were also discussed. This research filled the gap of the chemosensory genes of P. flammans and provided basic data for future functional molecular mechanisms studies on P. flammans olfaction.